Benthic biodiversity patterns in the deep Southwest Atlantic - Souza, Bruno Henrique de Moraes e (2025)
The deep sea (> 200m), the largest ecosystem on Earth, remains largely unexplored due to logistical and technological challenges derived from extreme environmental conditions. These areas are composed by a diversity of geological formations that harbor a mosaic of habitats with heterogeneous physicochemical aspects, supporting complex benthic communities with distinct biodiversity characteristics. Many deep-sea ecology studies are dedicated to finding and explaining the drivers of biodiversity patterns, such as low individual abundance and high species richness, primarily using taxonomic data. However, functional analyses, based on species traits that affect their survival and resourcs exploitation capabilities, are more effective in elucidating the relationships between the fauna and the ecosystem. Nevertheless, the taxonomic characterization of these communities is essential for revealing ecological patterns and assessing this functional biodiversity. This study aimed to assess and compare taxonomic and functional biodiversity by characterizing benthic communities in seven distinct habitats in the deep Southwest Atlantic (whale bones, wood parcels, carbonate mounds, Carbonate Mound Vicinities, pockmarks, Pockmark Buffer Areas, and salt diapirs) to determine the congruence between these approaches, the dominant ecological processes in each system, and to identify their differences. Results suggest that food availability is the primary factor regulating the structure of benthic communities, increasing the abundance and dominance of a few species and functionalities. Furthermore, interspecific relationships (competition) and environmental disturbances (stress) were also identified as important processes. In habitats with high energy availability and reducing conditions (whale bones, wood), competitive dominance and environmental filters select for species better adapted to utilize the available resources, resulting in lower taxonomic and functional biodiversity. On whale bones, for instance, this competition becomes evident in the analysis of substrates colonized by different specialists (Osedax spp. and Rubyspira spp.), which shape the communities in distinct ways. Conversely, where energy quantity is moderate, disturbance is low, and niche availability is high (carbonate mounds, pockmarks), resource partitioning and competitive exclusion are the predominant processes, increasing both measures of biodiversity. In food-limited environments (surroundings of carbonate mounds), one of the most severe environmental filters, biodiversity and abundance are restricted. Finally, environments regulated by environmental filters and with lower rates of biodiversity are more susceptible to natural or anthropogenic environmental changes, as few species perform unique ecosystem functions. Other studied habitats are hotspots of taxonomic diversity, harboring great richness of species. Considering that many of these habitats are located in areas of interest to the oil and gas industry, this study reinforces the urgent need to assess their biodiversity to inform more assertive management and conservation decisions